La enseñanza de la lengua de señas ecuatoriana y su adaptación al Marco Común de Referencia Europeo en Ecuador - Banet Ponce, Jorge Luis (2024)
This paper examines Ecuadorian Sign Language teaching from its beginning to the present time and its adaptation to the Common European Framework of Reference for languages by a higher education institution. It reviews the history of language teaching, the history of sign language teaching in the Ecuadorian context, and finally it proposes suggestions for its improvement. It argues that sign language, like any other natural language, should be taught communicatively by appropriately trained language teachers to obtain the best results. These teachers may be native or non-native, as it has already been argued in the teaching of other foreign and second languages. Furthermore, the teaching of Ecuadorian Sign Language should adhere to the guidelines of the Common European Framework of Reference for Languages, just as oral languages in the Ecuadoriancontext do.